2021
DOI: 10.3390/biomedicines9040420
|View full text |Cite
|
Sign up to set email alerts
|

Phaseolin Attenuates Lipopolysaccharide-Induced Inflammation in RAW 264.7 Cells and Zebrafish

Abstract: Kushen (Radix Sophorae flavescentis) is used to treat ulcerative colitis, tumors, and pruritus. Recently, phaseolin, formononetin, matrine, luteolin, and quercetin, through a network pharmacology approach, were tentatively identified as five bioactive constituents responsible for the anti-inflammatory effects of S. flavescentis. However, the role of phaseolin (one of the primary components of S. flavescentis) in the direct regulation of inflammation and inflammatory processes is not well known. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Therefore, KX may reduce inflammation through the TAB1/NF-κB pathway to reduce myocardial injury. Numerous modern pharmacological studies have previously shown that the Sophora flavescens family of TCM can reduce the levels of TNF-α and IL-1β in ethanol-induced acute gastric ulcer rat model and lipopolysaccharide-induced inflammation in zebrafish through the NF-κB signaling pathway (18,50,51). Combined with the findings of the present study, it was therefore hypothesized that Sophora flavescens alkaloids in KX may serve a therapeutic role in the first stage of EAM by inhibiting inflammatory responses.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, KX may reduce inflammation through the TAB1/NF-κB pathway to reduce myocardial injury. Numerous modern pharmacological studies have previously shown that the Sophora flavescens family of TCM can reduce the levels of TNF-α and IL-1β in ethanol-induced acute gastric ulcer rat model and lipopolysaccharide-induced inflammation in zebrafish through the NF-κB signaling pathway (18,50,51). Combined with the findings of the present study, it was therefore hypothesized that Sophora flavescens alkaloids in KX may serve a therapeutic role in the first stage of EAM by inhibiting inflammatory responses.…”
Section: Discussionsupporting
confidence: 67%
“…As a well-known typical Gram-negative bacterium, the endotoxin LPS has many biological activities, including an immune-enhancing effect. Activation of macrophages by LPS can enhance the production of inflammatory cytokines and mediators such as TNF-α, IL-6, and IL-10 [ 29 ]. In this study, MP showed a good proliferative effect on RAW264.7 cells ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used a cellular migration assay to examine the cellular migration ability of RAW 264.7 macrophages toward vascular endothelial cells with high-fat damage. The cellular migration assay has been clearly described in a previous report [ 39 ] (Hwang et al, 2021). Transwells (Corning, New York, NY, USA) with 8.0 μm pore size were used in this experiment for cell migration assays.…”
Section: Methodsmentioning
confidence: 99%